NEW LIQUID-CRYSTALLINE MATERIALS BY COMBINATION OF PYRAMIDIC AND CALAMITIC STRUCTURAL UNITS - BUDIG, H; DIELE, S; GORING, P; PASCHKE, R; SAUER, C; TSCHIERSKE, C (Journal of the Chemical Society. Chemical communications, 1994)
Fixing of calamitic rod-like molecules to a cyclotribenzylene unit gives liquid crystalline materials with either columnar or lamellar mesophases.